Magnetic flux leakage system for wire rope inspection using bluetooth communication - Salehhon, Muhammad Mahfuz (2014)
A wireless data communication Magnetic Flux Leakage (MFL) system for steel wire rope cable inspection has been designed and constructed to facilitate the remote data transferring. The system incorporates permanent magnets and Hall Effect sensor arrays, with its signal processing circuit and data acquisition system. Strong permanent magnetic discs of about 1T are used to magnetize the cable. Hall Effect sensors are arranged in parallel to detect the leakage flux from different angles. The system is battery operated, which is three units of AA batteries function as a power source. Another three units of AA batteries can also be fitted in as the backup power supply. The wireless data communication system has been constructed using Bluetooth module. The signals are digitized using an Emant380 Bluetooth data acquisition module consist of six channels of differential multiplexed analog-to-digital converter, and the data can be stored in computer or Smartphone’s memory. Python programming language is used to collect and interpret the data in a graphical form. This system use Tkinter graphical user interface toolkit for the computer while HTML is a platform for full screen user interface display on Smartphone. The screen displays the location and the flaws signal. System was tested and evaluated on various simulated wire rope defects of different depth and width, ranging from 2 mm to 6 mm depth and 1 mm width and also 2 mm to 6 mm width and 2 mm to 3 mm depth. This system has a relatively high sensitivity for the detection of magnetic flux leakage through defects with a depth of 2 mm and 1 mm wide.